Analysis of methodological presuppositions for life course studying: the problem of choice subjectivity - Zhao, Yuanlong; Filinskaya, Larisa V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article analyses the peculiarity of the psychological and sociological consideration of the concept of the life course. It is noted that initially the concept of a life course was introduced within the framework of psychological research, in which the main emphasis was placed on self-realisation and personality as a subject of one’s life course. At the same time, the subject was considered as a kind of autonomous unit that sets life goals for itself and selects the means to achieve them. The sociological approach fundamentally changes the point of view, making the dependence of the life course on the social context the subject of its consideration. This context has two main dimensions: ideological (value-normative) within which the institutionalisation of the life course takes place, as well as material, within which the objective determination of the life course is carried out depending on access to resources and on the position of the individual in the social space. Thus, society creates a mechanism of structural compulsion to choose a certain life trajectory.
Keywords: life course; life trajectory; biographical method; life scenario; social age